2018
DOI: 10.1177/1040638718765617
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal and scrotal carcinomas of unknown origin in two bovine calves

Abstract: Two unrelated bovine beef calves, aged 2 mo and 3 mo, were presented to The Ohio State University Veterinary Medical Center because of scrotal swelling and abdominal distension. On postmortem examination, there was abundant peritoneal fluid and numerous small friable masses covering all peritoneal surfaces and extending into the scrotum via the tunica vaginalis, with no identifiable primary neoplasm. Based on light microscopy, differential diagnoses included malignant mesothelioma and anaplastic carcinoma. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Immunohistochemistry revealed strong positive cytoplasmic immunoreactivity for pancytokeratin antibody clone AE1/AE3 (Figure 2(c)), while low numbers of individual or clustered neoplastic cells showed positivity for vimentin (Figure 2(d)). Together with the gross findings in the calf, these microscopic findings were considered confirmatory of a diagnosis of epithelioid mesothelioma (Munday et al 2017;Brakel et al 2018).…”
Section: Peer-reviewed Correspondencementioning
confidence: 75%
See 1 more Smart Citation
“…Immunohistochemistry revealed strong positive cytoplasmic immunoreactivity for pancytokeratin antibody clone AE1/AE3 (Figure 2(c)), while low numbers of individual or clustered neoplastic cells showed positivity for vimentin (Figure 2(d)). Together with the gross findings in the calf, these microscopic findings were considered confirmatory of a diagnosis of epithelioid mesothelioma (Munday et al 2017;Brakel et al 2018).…”
Section: Peer-reviewed Correspondencementioning
confidence: 75%
“…Mesotheliomas are reported to be the second most common neoplasm in calves after juvenile lymphoma (Brakel et al 2018), but, as stated earlier, are not a commonly reported cause of bovine dystocia. However, it is possible that the role of mesotheliomas in causing fetal ascites and dystocia has been overlooked since although these calves are invariably delivered by partial fetotomy, this does not always involve full incision of the calf's abdomen.…”
Section: Peer-reviewed Correspondencementioning
confidence: 84%
“…As neoplasias malignas das células de revestimento das cavidades mesoteliais que recobrem as membranas serosas e seus tecidos de suporte de origem mesodérmica são raras em bovinos (Brakel et al, 2018;Chen & Hsu, 2009;Ladds & Crane, 1976;Peli et al, 2018;Sutton, 1988;Wolfe et al, 1991). Esses tumores foram relatados em humanos (Fonseca et al, 2014;Priyadarshi et al, 2018), equinos (Johnson et al, 2008) e cães (Moran et al, 2001;Son et al, 2018), sendo que a maioria desses tumores foram encontrados no peritônio, na pleura e com menor frequência no pericárdio (Brakel et al, 2018;Peli et al, 2018;Wolfe et al, 1991). Neoplasias da túnica vaginal (uma extensão do peritônio que reveste os testículos) tem sido descrita em bovinos (Brakel et al, 2018;Ladds & Crane, 1976;Sutton, 1988).…”
Section: Introductionunclassified
“…Esses tumores foram relatados em humanos (Fonseca et al, 2014;Priyadarshi et al, 2018), equinos (Johnson et al, 2008) e cães (Moran et al, 2001;Son et al, 2018), sendo que a maioria desses tumores foram encontrados no peritônio, na pleura e com menor frequência no pericárdio (Brakel et al, 2018;Peli et al, 2018;Wolfe et al, 1991). Neoplasias da túnica vaginal (uma extensão do peritônio que reveste os testículos) tem sido descrita em bovinos (Brakel et al, 2018;Ladds & Crane, 1976;Sutton, 1988). Das neoplasias malignas, os mesoteliomas são os mais comuns, tanto em humanos quanto em animais (Priyadarshi et al, 2018).…”
Section: Introductionunclassified
“…Reported conditions involving the vaginal tunic in animals include mesothelioma in dogs, rats, stallions, bulls, and calves, and leiomyoma in a dog. 4,13,14,16,17,19,27,30 Non-neoplastic conditions affecting the vaginal tunics include hydrocele and hematocele. 9 Inflammatory conditions involving the testicular tunics are commonly reported and can be secondary to a disseminated infection caused by agents involved in polyserositis or extension of peritonitis in domestic animals.…”
mentioning
confidence: 99%